Chromatographic and spectroscopic studies on β-cyclodextrin functionalized ionic liquid as chiral stationary phase: Enantioseparation of NSAIDs - Nurul Yani Rahim; Kheng Soo Tay; Sharifah Mohamad (Adsorption Science & Technology)
Recently, we reported a new chiral stationary phase prepared using β-cyclodextrin functionalized with aromatic ionic liquid which is aimed to enhance the performance of enantioseparation of flavonoids and β-blockers. In this paper, the characteristics and performance of previously prepared chiral stationary phase denoted as β-CD-BIMOTs were compared with the newly synthesized chiral stationary phase denoted as β-CD-DIMOTs. β-CD-DIMOTs were prepared by functionalization of β-cyclodextrin with aliphatic ionic liquid. The obtained β-CD-BIMOTs and β-CD-DIMOTs stationary phases were compared with native β-CD stationary phase for the enantioseparation of non-steroidal anti-inflammatory drugs (NSAIDs) (ibuprofen, indoprofen, ketoprofen and fenoprofen). The β-CD-BIMOTs stationary phase showed greater chiral resolution capabilities rather than β-CD-DIMOTs and native β-CD stationary phases. Further, in order to understand the interaction of enantioseparation, the inclusion complex formation between NSAIDs and β-CD-BIMOTs was studied using 1 H NMR, NOESY and UV/Vis. The enantioseparated NSAIDs were found to form multiple interactions with β-CD-BIMOTs-CSP.